2014
DOI: 10.1246/cl.140099
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Process of Silica Hard-shell Microcapsule (HSMC) Containing Phase-change Materials

Abstract: A fabrication process via the double-emulsion method is proposed for silica hard-shell microcapsules (HSMCs) that contain trimethylolethane (TME) hydrate. The TME-encapsulating silica-HSMCs are promising materials for reusable phase-change materials for latent-heat transportation systems. The obtained silica-HSMCs were visualized by a scanning electron microscope. The amount of TME hydrate inside the capsules was confirmed using a differential scanning calorimeter. The measured latent heat of the TME-encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…reported the fabrication method of silica hard shell microcapsules containing paraffin. Toyoda et al (2014b) also reported that the fabrication of silica hard shell microcapsules containing trimethylolethane hydrates.…”
Section: Microcapsulementioning
confidence: 99%
See 3 more Smart Citations
“…reported the fabrication method of silica hard shell microcapsules containing paraffin. Toyoda et al (2014b) also reported that the fabrication of silica hard shell microcapsules containing trimethylolethane hydrates.…”
Section: Microcapsulementioning
confidence: 99%
“…Such a silica shell has advantages in mechanical strength, in chemical stability and it has low adsorption characteristics onto the metal walls. Additionally, it can be applied to the high temperature latent heat transportation because its melting point locates over 600 o C. Toyoda et al (2014b) made the silica microcapsules from the porous hollow microcapsules. This technology indicates any materials with the phase change temperature of lower than 600 o C can be inserted into the microcapsules.…”
Section: Microcapsulementioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption force between a hydrate and substrate might be significantly lower when a substrate is hydrophilic. 31,32) Therefore, crystals generated on the substrate will be easily removed into the slurry, resulting in the generation of a new crystal on the substrate, before it detaches from the surface. Thus, the crystals cannot grow to large sizes on the hydrophilic substrate.…”
Section: Crystal Growth Characteristicsmentioning
confidence: 99%